The Implementation of Authentic Assessment on 2013 Curriculum in Islamic Religious and Character Educational Learning at Purwokerto’s High School - Rohmad, Rohmad (International Conference of Moslem Society, 2016)
The change of purpose which become the aim on 2013 curriculum especially related to three domain of educational objectives also demand an evaluation development change. This friction have complicated implication with assessment system which is used and developed. The assessment system which is developed is an authentic assessment. Teachers have to develop the assessment system refer to real world and multi-technic using. The religious and character educational subject become the first of compulsory group on 2013 curriculum structure. The first placing has a purpose that the subject is very important which is related to national education goal Base on the problem background which is described before, the formulation problem is how the planning and implementation of 2013 curriculum authentic assessment on Islamic religious and character educational learning in SMA Purwokerto 1, 2, 4 and 5? The research method used descriptive qualitative method, because the research is conducted on natural setting. This kind of research has an important contribution to solve a problem or to decide an action which require some information. The collecting data use an interview, observation, and documentation techniques. The collected data is described and analyzed after the validation. The analysis is focused on the comparison in planning and implementation step in authentic evaluation. The research result show that the evaluation of Islamic religion and character educational subjects in Purwokerto’s High School use test and non-test technique. Test technique is used to measure learning result achievement on attitude and skill. The implementation show that a teacher have no complicated problem on planning, implementation, and processing the test technique result. Beside, non-test technique has problem on planning, implementation and processing the result.